Data from the DOM biodegradation along a hydrological continuum in permafrost peatlands - Payandi-Rolland, D (via Mendeley Data) (2020)
This file presents the original data used the article named: "Dissolved organic matter biodegradation along a hydrological continuum in permafrost peatlands" and published in the Journal Science of the Total Environment in 2020. THIS DATASET IS ARCHIVED AT DANS/EASY, BUT NOT ACCESSIBLE HERE. TO VIEW A LIST OF FILES AND ACCESS THE FILES IN THIS DATASET CLICK ON THE DOI-LINK ABOVE